Efeito da interação Rhizobium, micorrizas VA e fosfatos no desenvolvimento de mudas de sabiá, Mimosa caesalpiniaefolia Benth - Mendes Filho, Paulo Furtado (1985)
Two experiments were conducted under greenhouse conditions, on the Campus of the Federal University of Ceara, Brazil, to study the interaction among Rhizobium, mycorrhiza VA and phosphates with sabia (Mimosa caesalpiniaefolia Benth). [...]